Mathematical modelling of single particle biomass combustion under diffusion controlled condition - Santos, Stanley O. (Animo Repository, 1999)
The aim of this research was to model the combustion of a single particle biomass particle with a diameter of 20 mm. This model is limited to a diffusion-controlled condition. Three case scenarios were investigated. The first case involved a stagnant external condition. The second case involved a moderatelv turbulent condition and the third case also involved a moderately turbulent condition however with consideration of blowing parameters. The model was developed based on the following assumptions: a.) quasi-steady condition b.) constant fuel propertv c.) shrinking core model d.) decoupled system of mass and heat transfer This model investigates the behaviour of the burning particles in terms of the following: a. Burning rates and shrinking rates b.) Effect of various parameters (i.e. heat transfer coefficient, oxygen con-centration, devolatilization rate, surrounding conditions) on surface temperature of the particle. c.) Temperature profile of the burning particle. The model was computed using finite differencing technique. Relaxation method was also applied to calculate surface temperature. The model showed that the burning rate of the particle is generally affected by its external condition. Model results indicated that the burnout time for a 20mm wood particle was 325 seconds in the case of stagnant external conditions. While the burnout time decreased to 56 seconds and 76 seconds when the particle was subjected to a moderately turbulent condition taking into account blowing and non-blowing parameters respectively. The blowing parameters considered in the model (under Case 3 condition) shows that this parameter could either increase or decrease the burning rate of the particle. It was noted that if the dominant blowing factor was caused by the evolution of volatiles and moisture within the particle, the burning rate tends to decrease. On the other hand, if the dominant blowing factor was caused by external blowing, the burning rate was observed to be faster. The surface temperature was estimated in this model. It was observed that effect of surrounding condition were significant with surface temperature to be much higher in Case 2 and Case 3 conditions as compared to Case 1 condition. The model results also showed that surface temperature increase as the free stream oxygen concentration and ambient temperature were increased and decreased when heat transfer coefficient was increased. The temperature of the particle was mapped as function of radius. The following parameters were investigated namely: convection cooling and heat of pyrolysis and drying. It was noted that particle temperature was more sensitive to convection cooling than heat of pyrolysis and drying. The results from this model would serve as a reference for future development of the combustion model. This would also serve as a good starting point for model-ling of a more interactive and complicated system.